The Impact of CEO Overconfidence on Real Earnings Management: Evidence from M&A Transactions - Sawssen Khlifi; Ghazi Zouari (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - Does CEO overconfidence have an effect on the level of real earnings management (REM) in the mergers and acquisitions (M&A) context? Motivation - the relationship between the overconfident manager's behavior and REM in the context of M&A has gained momentum in the accounting and financial studies. In this context, the present work will enrich the literature on behavioral finance and REM in the M&A context. Idea - This study was to investigate the effect of overconfidence as part of the manager's cognitive characteristics on the level of REM in M&A context. Data - The data were collected from the annual reports of the companies to build an M&A database and the Thomson Reuters database for the other variables. This study used panel data analysis on a sample of 280 M&A deals of American listed firms indexed in the S&P500 between 2012 and 2018. The total sample was divided into two subgroups according to whether the companies are involved in M&A transactions (test sample) or not (control sample). Tools - To test study's hypotheses, we applied multiple regression analysis based on panel data using the annual reports and Thomson Reuters database. Findings - The main finding of this study is related to the positive effect of overconfident manager's behavior on REM in the M&A context. The results show that overconfident managers of acquiring and target companies manage their results upwards using REM. Contribution - The present study provides a new addition to the prior literature by exploring the contributions of behavioral finance in studying the reality and perspectives of the real earnings management in the presence of an overconfident manager's behavior in the M&A market.
Keywords: G34; M49; 650; CEO overconfidence; Real earnings management (REM); Mergers and Acquisitions (M&A)